Complete response of myeloid sarcoma with cardiac involvement to radiotherapy - Yang, Wen-Chi (J Thorac Dis, 2016)
We present a rare case of intracardiac myeloid sarcoma (MS) of acute myeloid leukemia (AML) and who responds completely well to low-dose radiotherapy. This 19-year-old young man initially presented with AML and received standard chemotherapy followed by allogeneic hematopoietic stem cell transplantation (HSCT). However, he developed intracardiac isolated MS relapse with the presentation of exertional dyspnea and superior vena cava (SVC) syndrome 3 years later. He then received radiotherapy with 24 Gy at a 12 daily fractions using forward “field in field” intensity modulated radiotherapy technique. He dramatically had improved clinical symptoms, and complete remission was achieved one month after completing radiotherapy. Our result is in line with anecdotal case reports showed that radiotherapy with 15 Gy in 10 fractions or with 24 Gy in 12 fractions resulted in good response and less toxicity of 2 cases of MS with cardiac involvement. These results indicate that a modest radiotherapy dose, 24 Gy, achieves good local control of MS with cardiac involvement.